Analisis Skala Ekonomis Industri Kerajinan Tas Kulit di Kota Denpasar - Rahadi, I Gusti Agung Bagus Indra; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 12, Desember 2015 (pp. 1445-1529), 2015)
In general industry of leather bag handmade in Denpasar have several constraints as follows the similiar industries that have strong capital still dominate in the processof marketing and production process, intense competition, and the un-optimal usage of labor, and it ishave effect on production.This study aimed tofind out the effect of funds and labors both in simultaneous and partial towards the industrial productions of leather bag handmade in Denpasar, and to describe the economic of scale and production characteristic of leather bag handmade industry in Denpasar, with multiple linear regression analysis technique then transformed into Cobb-Douglass model. The sample was 67 businessman as respondents. The result showed that the fund and the labors washave significant effect towards the industry of leather bag handmade both simultaneous and partial (p<0,05). The economic of scale the leather bag handmade industry in Denpasar in category ofincreasing return to scale because the total of regression coefficients was 1,484. The character of leather bag industry in Denpasar was the labor intensive its shown by regression coefficients of the labors was higher than the fund.
Keywords: economic of scale, industry, capital and labor